METAPHORICAL POLYSEMY AS A HUMOUR ENGINE IN ENGLISH AND RUSSIAN - Kendjaeva Zemfira (Bright Mind Publishing, 2026)
Humour often appears at the exact moment when a reader or listener realizes that the same word can be understood in two compatible, yet competing ways. This article examines that “double-access” effect through metaphorical polysemy – cases where a lexical item keeps a literal sense while also developing metaphor-based senses (e.g., physical sharp → intellectual sharp). I focus on English and Russian because both languages routinely conventionalize metaphor, but they do not always conventionalize the same source domains or the same pragmatic “safe zones” for joking. Building on semantic accounts of deliberate ambiguity in verbal humour and on research that links humour to two-plane meaning construction, I argue that metaphorical polysemy becomes humorous when context makes the literal frame briefly plausible, then forces reanalysis. Evidence from psycholinguistic ERP work on Russian ambiguity processing supports the claim that metaphorical senses can trigger measurable competition and reinterpretation – precisely the cognitive rhythm that jokes exploit.
Keywords: Metaphorical polysemy, humour, ambiguity, figurative meaning, incongruity, English, Russian, pragmatics, cultural scripts, lexical access.